Notch and NF-κB: Coach and Players of Regulatory T-Cell Response in Cancer - Ferrandino, Francesca; Grazioli, Paola; Bellavia, Diana; Campese, Antonio Francesco; Screpanti, Isabella; Felli, Maria Pia (Frontiers in Immunology, 2018)
The Notch signaling pathway plays multiple roles in driving T-cell fate decisions, proliferation, and aberrant growth. NF-κB is a cell-context key player interconnected with Notch signaling either in physiological or in pathological conditions. This review focuses on how the multilayered crosstalk between different Notches and NF-κB subunits may converge on Foxp3 gene regulation and orchestrate CD4+ regulatory T (Treg) cell function, particularly in a tumor microenvironment. Notably, Treg cells may play a pivotal role in the inhibition of antitumor immune responses, possibly promoting tumor growth. A future challenge is represented by further dissection of both Notch and NF-κB pathways and consequences of their intersection in tumor-associated Treg biology. This may shed light on the molecular mechanisms regulating Treg cell expansion and migration to peripheral lymphoid organs thought to facilitate tumor development and still to be explored. In so doing, new opportunities for combined and/or more selective therapeutic approaches to improve anticancer immunity may be found.